Rapid Direct Detection and Differentiation of Mycobacterium tuberculosis complex in Sputum by Real-Time PCR - Saad Abdulsahib, Sabah; Abdulrazak Al-kazaz, Abdul Kareem; Al-Faham, Mohammad A. (Iraqi Journal of Science, 2023)
Tuberculosis status as the second leading causes of significant morbidity and mortality from an infectious disease worldwide, after human immunodeficiency virus (HIV). Sample collection was conducted at the Institute of Chest and Respiratory Diseases/Baghdad Medical City in Baghdad. The collection interval was from August to October 2014, 629 suspected TB patients were examined during this period. The results revealed among total 629 specimens, 56 (8.9%) of the specimens were positive by direct examination and 573 (91.1%) negative specimens by smear microscopy. Fifty six DNA samples were extracted from positive ZN smears of sputum specimens and 40 samples from healthy persons (as control) were subjected to molecular diagnosis by real time PCR to detect and differentiate of M. tuberculosis, M. bovis and M. bovis BCG. The results were clarified that the 48 samples (85.72%) were M. tuberculosis, 2 samples (3.57%) were mixed of M. tuberculosis and M. bovis, no M. bovis BCG was detected, and 6 (10.71%) were negative. These findings propose that M. bovis plays a minor role compared to M. tuberculosis in the etiology of pulmonary tuberculosis in Baghdad.